Kapitalrendite von Großcontainerschiffen. - Müller, Malte; Schönknecht, Axel (Deutscher Verkehrs-Verlag, 2005)
Um die Kapitalrendite verschiedener Containerschiffstypen zu quantifizieren und damit Antworten auf die Frage zu finden, ob es sich lohnt, in immer größere Containerschiffstypen zu investieren, wurde an der Technischen Universität Hamburg-Harburg (TUHH) in Zusammenarbeit mit der Forschungsgemeinschaft für Logistik e.V. (FGL) eine umfangreiche Untersuchung durchgeführt. Die Untersuchungsmethode, Kosten- sowie Einnahmenmodell und die Ergebnisse werden dargelegt. difu

To be able to quantify the returns for capital investment in container ships of different types, and to answer questions regarding the advantage of investing in ever larger container ships, the TUHH (Technische Universität Hamburg-Harburg) has carried out a thorough investigation, in cooperation with the FGL (Forschungsgemeinschaft für Logistik e.V.). Using the 'multi-port system' as a base, the yearly operating costs and revenue potential of today's and future container ships - classified according to the 1,000 TEU division - have been calculated for three different spheres of operation. The main result of this investigation shows that the return for capital investment in container ships reaches its peak at about 8,000 TEU. Ships larger than this only offer lower financial returns within the framework of the present system. For container ships of over 8,000 TEU, the 'hub feeder system' can conceivably turn out to be a more profitable mode of operation in future. difu
Keywords: Wasserverkehr; Verkehr; Güterverkehr; Verkehrswirtschaft; Containerverkehr; Kapitaleinsatz; Rendite; Wirtschaftlichkeit; Untersuchung; Modell; Containerschiff; Schiffsgröße; Schiffstyp; Frachtschiff; Containertransport; Güterverkehrsmarkt